One-Pot Copper-Catalyzed Three-Component Reaction of Sulfonyl Azides, Alkynes, and Allylamines To Access 2,3-Dihydro-1H-imidazo[1,2-a]indoles - Jin, Hongwei; Liu, Daohong; Zhou, Bingwei; Liu, Yunkui (Synthesis, 2020)
A copper-catalyzed multicomponent reaction of sulfonyl azides, alkynes, and allylamines affording 2,3-dihydro-1H-imidazo-[1,2-a]indoles in moderate yields is reported. Four C–N bonds are constructed by way of azide-alkyne cycloaddition (CuAAC) and double Ullmann-type coupling reactions in a one-pot process.
Keywords: multicomponent reaction; copper catalysis; azide-alkyne cycloaddition; Ullmann coupling reaction; 2,3-dihydro-1H-imidazo[1,2-a]indoles